Towards single photon detection with a practical EMCCD - Chen, Jingsi (2010)
The stochastic transfer function (STF) is a metric for imaging of a microscope that includes the idea of noise, this project attempted to obtain the STF by Monte Carlo method with photon counting device. In this project, a very sensitive Electron-multiplying CCD (EMCCD) camera is evaluated for its photon counting performance on STF measurement. The evaluation system employs a beam with a very weak intensity laser to illuminate the EMCCD, the output signal and background noise of the EMCCD is recorded and statistical data is obtained. The EMCCD output signal distribution under different conditions is given by a simulation. Moreover, photon counting in TIRF with fluorescent beads is also carried out to simulate the practical STF measurement condition. Although the experiment results suggest that the EMCCD camera used in this project is not capable of performing photon counting for the Monte Carlo method, the performance of this EMCCD camera is studied in detail. The evaluation method and data can be used to evaluate other EMCCD or photon counting devices.